The relationship between consumption of soy milk and the menstrual cycle of midwifery students - Handayani, Tri Restu; Contesa, Lina (International Journal on ObGyn and Health Sciences, 2023)
One of the reproductive health problems that can trigger infertility is ovulation disorders. The clinical manifestation of this disorder is irregular menstruation. The cause is a deficiency of the hormone estrogen. Soybeans are plants that contain high phytoestrogens which can meet the needs of estrogen in the body. This study aims to determine the relationship between soy bean consumption and the menstrual cycle. The research design used was an experiment with a pretest-posttest design. The sampling technique used purposive sampling consisting of 30 respondents who fit the inclusion criteria. Data analysis used the paired sample t-test with the Wilcoxon test. The normality test results obtained a pretest value of 0.344 and a post test value of 0.222. respondent data is normally distributed. The dependent t test results obtained a p value of 0.004 < 0.05. There is a relationship between soy milk consumption and the menstrual cycle. there is a change in the regularity of the menstrual cycle after consuming soy milk. Suggestion: women with irregular menstrual cycle problems can consume soy milk as an alternative to complementary medicine in preventing early infertility